IDENTIFICATION OF THE DOMAIN PROCESS INTERSECTIONS BETWEEN COBIT 4.1 AND COBIT 5 IN THE DETERMINATION OF IT GOVERNANCE ASSESSMENT - Nurtrisha, Widyatasya Agustika (LPPM Universitas Nusa Mandiri, 2021)
The implementation of information technology has an essential role in organizational development to support a business process. Currently, information technology is widely adopted by the organization. It is believed to help improve the efficiency of the ongoing business process so that IT management is needed in a more structured. Thus, need a guideline that can guide IT governance so it can be measured and utilized. COBIT is one of the frameworks that can utilize in providing IT governance guidelines for organizations, and it is the main reference used in implementing IT governance in organizations. Still, the assessment process takes a long time because many processes are assessed. So conducted this research to determine the similar activities between COBIT 4.1 and COBIT 5 as the basis for determining the development of an organizational assessment process that the organization will carry out to see the efficiency of the assessed process domain. This research is focused on several organizations that have carried out IT governance assessments with COBIT 4.1 and will then implement the assessment process using COBIT 5. Still, it will usually take more time and effort if done separately to streamline the assessment process and identify domain intersects. The process from COBIT 4.1 and COBIT 5 so that the effort to carry out the assessment can be more streamlined. Thus, this research will produce a study result related to which activities intersect with each other to determine the IT governance assessment in an organization.